Worldwide consumption of functional foods: a systematic review. (9th October 2014) - Ozen, Asli E; Pons, Antoni; Tur, Josep A
Abstract : The present systematic review was performed to assess differences in the worldwide consumption of functional foods. The Medline and Scopus databases were used to search the existing literature. A total of 23 studies that examined functional food consumption and included information on the country, gender, and age of participants were identified for inclusion. The studies investigated a variety of functional foods, and analysis of the findings indicates it is not possible to reach generalized conclusions about consumer choices regarding functional food consumption. Gender, age, level of education, and personal health status may each predict consumption of one or more functional foods. Further studies aimed at gaining a better understanding of the factors that influence consumption of functional foods are needed.